The Translated Editions of Dante’s Commedia in Brazil in the 20th Century: Translators and Preface Writers - Cechinel, Fernanda Moro; Gaspari, Silvana De (Revista de Italianística, 2023)
The work Commedia, written by the Florentine Dante Alighieri probably in the beginning of the 14th century, in the not yet unified Italy, had its first public version translated to Brazilian Portuguese, it is believed, around 1843, in the city of Rio de Janeiro, in the work Ramalhete poético do parnaso italiano, by the doctor, poet and translator Luiz Vicente De Simoni (HEISE, 2007). However, it was in the 20th century that the work was translated and edited at large in Brazil. This article aims at continuing the publicity of some of the results from the doctoral research that is being developed in the Programa de Pós-Graduação em Literatura (PPGLit), in the Universidade Federal de Santa Catarina (UFSC), developed with Capes/DS aid. In general, the research approaches the role of some paratexts (GENETTE, 2009), such as preface, postface, back cover, and flap, in the reading of a literary work. However, our objective with this text will be to present a panorama of the Brazilian editions of Dante’s Commedia in the 20th century, bearing in mind their translators and preface writers. In the current research level, 13 editions catalogued by the Dicionário de Literatura Italiana Traduzida (DLIT) were chosen. To achieve the objective, first it will be presented a brief reflection about this space occupied by the written word in the construction of the unified Italy, as well as the role of the written and translated word in the consolidation of the editorial market in Brazil. Then, with the information obtained from the translators and preface writers, most of them from the paratext material presented in the researched editions, we will trace an initial profile of these publications, bearing in mind the contact points and the divergences between them.